Challenges in Contract Murder Investigations - BEKISHEV, Askhat K.; IBRAYEVA, Alua; SMANOVA, Akmaral; NUSSIPOVA, Lyatifa; KAN, Aleksandr G. (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019, 2019)
The research dwells on the issues of combating contract murders, in particular, investigation-related issues, interactions between the police and other law enforcement agencies and aspects of certain investigative activities. The authors study the specifics of this crime type and its reasons. They reveal criminalistic features of contract murders, including a crime situation and the identity of victims and offenders. The authors also examine scientific works related to counteracting contract murders, analyze different scientific opinions and develop an algorithm for investigating this type of crimes. They provide examples of law enforcement and focus on the investigation of contract murders. As a result, certain recommendations for investigating and preventing contract murders are given.